Overview of Quality of School Life in High Schools in the City of Cilegon - Mulya, Handy Prasetya (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2023)
The quality of school life is a synthesis of positive and negative experiences, and other feelings that are specifically related to school life and affect student learning outcomes. Students who have a positive view of the quality ofschool life will be more involved in the learning process and will achieve better performance. The purpose of thisstudy is to describe the quality of school life in high schools in the city of Cilegon, Banten. This research is a quantitative descriptive. The subjects of this study were students of class X, XI, and XII in four high schools in Cilegon, Banten, totaling 1407 students. From the results of the study it can be concluded that the quality of school lif in state high schools in Cilegon City is relatively high withan mean empirik of 2.8150. However, based on information obtained from the subject, it is known that there are some things that need to be improved by the school so that students can get better learning outcomes and higher achievement, such as facilities at school, relationships between students, and the attention given by the teacher to students at school.